A comparative study on slurry erosion behavior of HVOF sprayed coatings (2017)
In actual work, slurry erosion behavior of three different HVOF sprayed cermet coatings has been studied. The coatings were developed using the powders feedstock having WC fine structured sizes, Cr3C2-NiCr 75-25 and NiCrWSiFeB, latter conventional grain sizes. The slurry erosion testing was performed using a laboratory made pot-type slurry erosion tester, at an impact velocity of 3.61m/s and 9.33 m/s and impact angle of 30 and 90º. The mechanism of material removal in slurry erosion was studied and discussed on microstructural investigations and mechanical properties under the erosion conditions. It was observed that the WC-CoCr cermet coating with fine WC grain exhibits higher erosion resistance as compared to conventional cermet coating due to its improved properties like low porosity, high micro-hardness and fracture toughness.